DIGITALIZATION OF SUPPLIER COLLABORATION IN SCM - Yadav, Suryakant (My University, 2019)
The supply chain is a complex system where supplier collaboration is not fully or partially integrated and optimized that makes it difficult to properly manage it. Taking in consideration previous research on this topic and insights from data collected from 16 suppliers, the analysis of results suggest that the digitalization of supplier collaboration process is a means to achieve such integration and optimization to enhance transparency, visibility and communication throughout the supply chain network. Hence, a company requires a roadmap for businesses to initiate a digitization-based collaboration with their suppliers, critical success factors to assess the digitization progress and KPIs to measure the performance of the digitization for successful digitized supplier collaboration. A case study in conjunction with the survey is used as the research methodology for this thesis. Additionally, 2 simulation models: three-point estimation and Monte Carlo simulation have been presented to measure the reliability of delivery time, resources and workforce needed for a company respectively. This thesis is concluded with suggestions for the company along with possibilities for future research.
Keywords: Digitization; Supplier collaboration; Digitization roadmap; Digitization success factor; Key performance indicator; three-point estimation model; Monte Carlo simulation model.